2000
DOI: 10.1002/1529-0131(200006)43:6<1233::aid-anr6>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Human cartilage gp‐39+,CD16+ monocytes in peripheral blood and synovium: Correlation with joint destruction in rheumatoid arthritis

Abstract: CD16+ monocytes, a cellular source of HC gp-39 in vivo, are overrepresented in both RA peripheral blood and synovial tissue. The presence of HC gp-39+ cells in RA synovium is correlated with the degree of joint destruction. These data support a role of these cells in the local autoimmune response that leads to chronic inflammation and joint destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
1
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 26 publications
2
129
1
1
Order By: Relevance
“…Previously we demonstrated that HC gp-39 is not expressed exclusively in articular cartilage but is found also in inflamed synovium and that the synovial membrane is a privileged site for presentation of this protein to the immune system (6,14,19). In immunohistochemistry analyses for MIA in the present study, collected biopsies described previously (14,19,29,33) were used to investigate local expression of MIA in the synovium, with mAb 14A.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Previously we demonstrated that HC gp-39 is not expressed exclusively in articular cartilage but is found also in inflamed synovium and that the synovial membrane is a privileged site for presentation of this protein to the immune system (6,14,19). In immunohistochemistry analyses for MIA in the present study, collected biopsies described previously (14,19,29,33) were used to investigate local expression of MIA in the synovium, with mAb 14A.…”
Section: Resultsmentioning
confidence: 68%
“…Additional SF samples from RA, SpA, and osteoarthritis (OA) patients originated from a previous study (28). Synovial membrane biopsy specimens from another group of patients (described in previous reports [14,19,29]) were obtained for immunohistochemistry studies. Eight biopsy samples per patient (17 RA, 13 SpA, 6 OA), obtained from an inflamed knee joint by needle arthroscopy (30), were studied.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations